Nickel-Catalyzed Photodehalogenation of Aryl Bromides - Higginson, Bradley; Sanjosé-Orduna, Jesus; Gu, Yiting; Martin, Ruben (Synlett, 2021)
Herein, we describe a Ni-catalyzed photodehalogenation of aryl bromides under visible-light irradiation that utilizes tetrahydrofuran as hydrogen source. The protocol obviates the need for exogeneous amine reductants or photocatalysts and is characterized by its simplicity and broad scope, including challenging substrate combinations
Keywords: nickel; photochemistry; dehalogenation; reduction; deuteration